2007
DOI: 10.1016/j.immuni.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Regulation of Lck Kinase Phosphorylation Sites by CD45 Is Critical for T Cell Receptor Signaling Responses

Abstract: The molecular mechanisms whereby the CD45 tyrosine phosphatase (PTPase) regulates T cell receptor (TCR) signaling responses remain to be elucidated. To investigate this question, we have reconstituted CD45 (encoded by Ptprc)-deficient mice, which display severe defects in thymic development, with five different expression levels of transgenic CD45RO, or with mutant PTPase null or PTPase-low CD45R0. Whereas CD45 PTPase activity was absolutely required for the reconstitution of thymic development, only 3% of wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
189
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(211 citation statements)
references
References 52 publications
20
189
0
2
Order By: Relevance
“…1 C and D). This is consistent with our previous findings in allelic series thymocytes as well as independent reports with other transgenic lines (29,30).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…1 C and D). This is consistent with our previous findings in allelic series thymocytes as well as independent reports with other transgenic lines (29,30).…”
Section: Resultssupporting
confidence: 94%
“…We and others have shown that CD45 plays a negative regulatory role as well as a positive regulatory role during TCR signaling by dephosphorylating the activation loop as well as the inhibitory tyrosine of Lck (29,30). Whether an analogous negative regulatory role exists in B cells is unclear, however (31).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…2B). As reported (19,20), phosphorylation of the C-terminal and autocatalytic tyrosines was increased in KO thymocytes. Surprisingly, there was a modest increase in phosphorylation of the C-terminal tyrosine and a more marked increase in phosphorylation of the autocatalytic tyrosine in WEDGE thymocytes.…”
Section: Resultssupporting
confidence: 85%
“…Below this threshold, only the positive effects of CD45 phosphatase activity may be appreciated. This reasoning may explain why even very low levels of a CD45 transgene reconstitute thymic development in CD45 null mice (20). However, these studies did not evaluate the T cell repertoire at a qualitative level.…”
Section: Discussionmentioning
confidence: 99%